Recent Shifts in Capital Flow Patterns in Korea : An Investor Base Perspective - Hansen, Niels-Jakob.; Krogstrup, Signe (Washington, D.C. : International Monetary Fund, 2019)
Koreas cross border capital flows have tended to respond negatively in global risk-off episodes, resulting in volatility in the foreign exchange market and occasional policy responses in the form of foreign exchange interventions. We study the relationship between Korean capital flows and global volatility up to 2018. The response of capital flows during risk-off episodes have become more muted over time, and occasional safe-haven type flows into Korean bond markets have helped counterbalance the tendency for portfolio investors to leave. We describe these changing patterns and relate them to shifts in Korea's domestic investor base. We discuss whether they reflect a sustained shift in the sensitivity of Koreas capital flow pressures to global risk-off episodes, and implications for monetary and exchange rate policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet